Voltammetric studies on vitamin K1 in organic solvents - Hui, Yan Lan (2011)
Vitamin K1 (VK1) was shown by voltammetry to undergo two chemically reversible one-electron reduction processes in organic solvents containing Bu4NPF6 as the supporting electrolyte. The potential separation between the first and second electron transfer steps diminished sequentially with the addition of water. The voltammetric behavior was interpreted based on the degree of hydrogen-bonding between the reduced forms of VK1 with water in the solvents. It was found that the potential separation between the first and second processes was especially sensitive to water in the low molar levels (0.001 – 0.1 M), therefore; by measuring the peak separation as a function of controlled water concentrations (accurately determined by Karl Fischer coulometric titrations) it was possible to prepare calibration curves of peak separation versus water concentration. The water content of the solvents was accurately measured using KF coulometric titrations. Calibration data were obtained which are independent of the nature of the reference electrode, and allow the water content of the solvents to be calculated by performing a single voltammetric scan in the presence of VK1 and 0.2 M supporting electrolyte (Bu4NPF6).